Monoclonal antibodies for the induction of transplantation tolerance. - Waldmann, H; Cobbold, S (1993)
Non-lytic antibodies to CD4 and certain other T cell adhesion receptors can guide the immune system to become tolerant to foreign antigens, and to regain tolerance in autoimmunity. Tolerance is maintained lifelong through the action of regulatory T cells that in turn can influence naive T cells to acquire the same regulatory properties. A fuller understanding of the molecular basis of infectious tolerance could lead to the design of better immunosuppressive protocols.